Comprehensive Evaluation of Reference Values of Parametric and Non-Parametric Effect Size Methods for Two Independent Groups - Tak, Ayşegül Yabacı; Ercan, Ilker (International Journal of Statistics in Medical Research, 2022)
In the field of health and other sciences, effect size (ES) provides a scientific approach to the effectiveness of treatment or intervention. The p-value indicates whether the statistical difference depends on chance, while ES gives information about the effectiveness of the treatment or intervention, even if the difference is not significant. For this reason, ES has become a very popular measure in recent years. It depends on which ES will be used based on the distribution of data and the number of groups. In this study, parametric and non-parametric ES were evaluated for two independent groups. When the literature was examined, there were no studies aimed at evaluating the reference values of the parametric and non-parametric ES methods used for two independent groups. In this study, the reference values of parametric and non-parametric ES methods for two independent groups were re-evaluated by a simulation study. As a result, the very small reference value of parametric ES methods was determined differently from the literature. It has been seen that the reference values of non-parametric ES methods are valid in cases where the skewness is low, and new reference values have been proposed at the varying skewness level.